Define “First”: In Defence of the Children - Pierre, Phaedra (Daily Express, 2008)
This article takes issue with a newspaper article that lauded a particular Carnival band as the first "green" Carnival band. It argues that since Carnival became a part of the school system, teachers, students, and parents have used eco-friendly themes for individual portrayals, bands, and festival celebration themes
Keywords: Environmental awareness; Carnival arts; Primary schools; Secondary schools; Recycling; Trinidad and Tobago